Transition metal oxide nanoparticles: Potential nano-modifier for rocket propellants. (1st November 2016) - Dave, Pragnesh N.; Ram, Pravin N.; Chaturvedi, Shalini
ABSTRACT: TiO2, ZnO2, and CrO2 nanoparticles were prepared by novel quick precipitation method, where transition metal oxides were used as catalyst. All nanoparticles were characterized by x-ray diffraction (XRD) and scanning electron microscopy (SEM). The average particle size for TiO2, ZnO2, and CrO2 was 44.8, 13.4, and 77.6 nm, respectively. Catalytic properties of these nanomaterials were studied using ammonium perchlorate (AP)/hydroxy-terminated polybutadiene (HTPB) propellant by thermogravimetric analysis (TGA) and differential thermal analysis (DTA). Both experimental results reveal that there is an increase in the thermal decomposition of propellants in the presence of transition metal oxide nanoparticles. Activation energy of high-temperature decomposition (HTD) of propellant with transition metal oxide nanoparticles was calculated by Kissinger equation. Burning rates of propellants were also calculated.